Analisis Hukum Kasus Gugatan Wanprestasi Pembatalan Perjanjian Pengikatan Jual Beli (PPJB) (Study Kasus Putusan Nomor: 346/Pdt.G/2016/PN.Tng.) - Yudhistya Yudhistya; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Official agreements must be drafted according to the provisions of chapter 1320 of the Civil Code. agreement. Binding Agreement of Sale and Purchase (PPJB) of land and buildings made by PT. BSD to PT. SGU is a preliminary agreement that precedes land and construction transactions which are requested to cancel the agreement by PT. BSD because PT. SGU is considered to have defaulted. Cancellation of the Purchase Binding Agreement (PPJB) as contained in the Decision Number: 346 / Pdt.G / 2016 / PN.Tng. Based on this background there are interesting things to discuss in writing this thesis, namely whether or not the PPJB PT. BSD and PT. SGU as well as the judge's judgment when determining the case. This study uses normative juridical research methods. legal material used consists of primary and secondary legal material. The conclusion from the research stated that PPJB of land and buildings between PT. BSD with PT. SGU has completed the characteristics of an agreement whereby the provisions of Chapter 1320 of the Civil Code and judges' judgment when determining the case are the cancellation clauses by the parties in the event of default in the PPJB not because the terms of the agreement are not fulfilled. Suggestions from the author for the strength of the agreement every PPJB making should be made before a notary public and any disputes that arise can be resolved by deliberation to reach consensus.